Rethinking Social Upgrading in Global Value Chains: Worker Power, State‒Labour Relations and Intersectionality - Kristoffer Marslev; Cornelia Staritz; Gale Raj-Reichert (Development and Change, 2022)
This article builds on critiques of the concept of social upgrading in global value chain (GVC) research, which problematize its coupling to lead firm strategies and economic upgrading by supplier firms, by reconceptualizing social upgrading through the lens of worker power. It argues that a better understanding of the causal processes of social upgrading can be obtained by integrating insights from labour geography, which situates worker agency at the intersection of a 'vertical' dimension of transnational relations and a 'horizontal' dimension of local relations, with conceptualizations of worker power from (global) labour studies, particularly the modes of structural and associational power. The authors call for a deeper theorization of the places in which GVCs 'touch down', arguing that worker power is decisively shaped by state–labour relations as well as the intersectionality of worker identities and interlinkages between spheres of production and reproduction. Case study analyses of the apparel sectors in Cambodia and Vietnam employ this reconceptualization, drawing on the authors' own fieldwork. In both cases, worker power expressed in strike action was a key causal driver of social upgrading; and in both, the outcomes were conditioned by GVC dynamics as well as shifting state–labour relations and intersections of worker identities linked to gender, household and community relations.
Keywords: 300